2021
DOI: 10.1038/s41598-021-82840-x
|View full text |Cite
|
Sign up to set email alerts
|

Predictive modeling of clinical trial terminations using feature engineering and embedding learning

Abstract: In this study, we propose to use machine learning to understand terminated clinical trials. Our goal is to answer two fundamental questions: (1) what are common factors/markers associated to terminated clinical trials? and (2) how to accurately predict whether a clinical trial may be terminated or not? The answer to the first question provides effective ways to understand characteristics of terminated trials for stakeholders to better plan their trials; and the answer to the second question can direct estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 24 publications
2
37
2
Order By: Relevance
“…Overall, embedding features are least informative. This is different from our previous study [10], where statistics features are found to be more informative than keyword features and embedding features. Nevertheless, our experiments in the next section will show that, despite of the individual importance, all four types of features contribute to the accurate prediction of COVID-19 trials.…”
Section: Plos Onecontrasting
confidence: 99%
See 4 more Smart Citations
“…Overall, embedding features are least informative. This is different from our previous study [10], where statistics features are found to be more informative than keyword features and embedding features. Nevertheless, our experiments in the next section will show that, despite of the individual importance, all four types of features contribute to the accurate prediction of COVID-19 trials.…”
Section: Plos Onecontrasting
confidence: 99%
“…These models can also be applied to current or planned trials to understand their probability of completion vs termination. Previous termination prediction studies [15,16], along with our previous research [10] demonstrate the predictive power of structured and unstructured variables in order to predict if a clinical trial is likely to terminate.…”
Section: Related Workmentioning
confidence: 88%
See 3 more Smart Citations